SISTEM INFORMASI ONLINE PAYMENT BERBASIS WEBSITE PADA TOKO ONLINE DOC SEEKER MENGGUNAKAN FRAMEWORK LARAVEL - Rizqy Nabila (2023)
The development of technology is currently very rapid, for businesses it turns out to be very influential, namely by making transactions online. This online transaction is very profitable for customers because it can make payments easier, and also shortens the time. In addition, online transactions are also very profitable for sellers to improve shop performance. Even though online transactions are widely misused by some parties to commit fraud or scams for payment. This website will be made as modern as possible with various features that are rarely available on other shop websites, namely using payment via e-wallet via MidTrans. So, customers don't need to upload proof of payment on the website. It is hoped that with this information system, it will make it easy for customers to make transactions and pay for purchases of goods available on this website without the need to make transactions via private chat.